The Growth and Human Capital Structure of New Firms over the Business Cycle - Martin Murmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Recent research based on aggregate data suggests that employment in young firms is more negatively impacted during economic crises than employment in incumbent firms. Using firm-level data, we show that under constant human capital of the firms' founders, employment growth in less than 1 1/2-year-old start-ups reacts countercyclically and employment growth in older start-ups reacts procyclically. The young start-ups realize their countercyclical growth by hiring qualified labor market entrants.
Keywords: E32; J23; L26; M13; L25; L11; D22; 330